2015
DOI: 10.4103/1119-3077.163278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hibiscus sabdariffaon blood pressure and electrolyte profile of mild to moderate hypertensive Nigerians: A comparative study with hydrochlorothiazide

Abstract: HS was a more effective antihypertensive agent than HCTZ in mild to moderate hypertensive Nigerians and did not cause electrolyte imbalance. HS showed longer duration of action compared to HCTZ and reduction in serum Na+ may be another antihypertensive mechanism of action of HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…The characteristics of included studies are outlined in Table . In summary, seven trials (Asgary et al, ; Chang et al, ; Gurrola‐Díaz et al, ; Kafeshani et al, ; Kuriyan, Kumar, Rajendran, & Kurpad, ; McKay et al, ; Nwachukwu et al, ) consisting of 362 unique participants with mean age of 44 years old were included in the pooling analysis. Studies were conducted in Iran (Asgary et al, ; Kafeshani et al, ), Taiwan (Chang et al, ), India (Kuriyan et al, ), the United States (McKay et al, ), Nigeria (Nwachukwu, Aneke, Nwachukwu, et al, ), and Mexico (Gurrola‐Díaz et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of included studies are outlined in Table . In summary, seven trials (Asgary et al, ; Chang et al, ; Gurrola‐Díaz et al, ; Kafeshani et al, ; Kuriyan, Kumar, Rajendran, & Kurpad, ; McKay et al, ; Nwachukwu et al, ) consisting of 362 unique participants with mean age of 44 years old were included in the pooling analysis. Studies were conducted in Iran (Asgary et al, ; Kafeshani et al, ), Taiwan (Chang et al, ), India (Kuriyan et al, ), the United States (McKay et al, ), Nigeria (Nwachukwu, Aneke, Nwachukwu, et al, ), and Mexico (Gurrola‐Díaz et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Except Kafeshani et al (), all studies enrolled both gender. Participants' health conditions were different among studies: Two studies recruited patients with hypertension (McKay et al, ; Nwachukwu, Aneke, Nwachukwu, et al, ), one study included patients with metabolic syndrome (Asgary et al, ), two studies enrolled healthy adults (Kafeshani et al, ; Kuriyan et al, ), one trial included obese adult with fatty liver (Chang et al, ), and one study involved both healthy and metabolic syndrome patients (two separate participant groups (Gurrola‐Díaz et al, ). Dose of supplementation and duration of follow‐up varied between studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of clinical trials assayed with HS extracts show the antihypertensive effectiveness of this extract in patients with metabolic syndrome and hypertension. According to most studies, the antihypertensive effect of HS extract is related to the inhibition of angiotensin I-converting enzyme (ACE) and a reduction in serum sodium levels [41,42]. Nevertheless, Joven et al suggested that the inhibition of ACE activity contributes in a lesser degree and that the antioxidant, anti-inflammatory and endothelium-dependent effects are, most likely, the mechanisms involved in the hypotensive effect of HS [21].…”
Section: Biological Activitiesmentioning
confidence: 99%